Posterior basolateral amygdala to ventral hippocampal CA1 drives approach behaviour to exert an anxiolytic effect - Guilin Pi; Di Gao; Dongqin Wu; Yali Wang; Huiyang Lei; Wenbo Zeng; Yang Gao; Huiling Yu; Rui Xiong; Tao Jiang; Shihong Li; Xin Wang; et al. (Nature Communications, 2020)
Projections from the anterior and posterior basolateral amygdala (pBLA) to the ventral hippocampus CA1 (vCA1) are heterogenous. Here the authors show that activating the pathway from pBLA to vCA1 calbindin 1 positive neurons has an anxiolytic effect in approach-avoidance tasks in mice.